2022
DOI: 10.1200/jco.21.02091
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sintilimab Plus Anlotinib for PD-L1–Positive Recurrent or Metastatic Cervical Cancer: A Multicenter, Single-Arm, Prospective Phase II Trial

Abstract: PURPOSE No combined immunotherapy and antiangiogenic therapy have been investigated in exclusively programmed death-ligand 1 (PD-L1)–positive advanced cervical cancer (CA). We investigated the efficacy and safety of sintilimab plus anlotinib as second-line or later therapy for PD-L1–positive recurrent or metastatic (R/M) CA. PATIENTS AND METHODS Patients with PD-L1–positive (Combined Positive Score ≥ 1) R/M CA who progressed after at least one prior systemic chemotherapeutic regimen or could not tolerate chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
61
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 28 publications
12
61
2
Order By: Relevance
“…Therefore, based on this consideration, we expect that this patient would also benefit from the combination of immune checkpoint inhibitors with antiangiogenic drugs for survival. In advanced NSCLC [ 29 ] and cervical cancer [ 30 ], sintilimab, in combination with anlotinib, exerts synergistic antitumor effects. However, treatment of advanced Ca ex PA with immunotherapy plus antiangiogenic therapy is not yet reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on this consideration, we expect that this patient would also benefit from the combination of immune checkpoint inhibitors with antiangiogenic drugs for survival. In advanced NSCLC [ 29 ] and cervical cancer [ 30 ], sintilimab, in combination with anlotinib, exerts synergistic antitumor effects. However, treatment of advanced Ca ex PA with immunotherapy plus antiangiogenic therapy is not yet reported.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthily, plenty of clinical trials are exploring the combination strategies of angiogenesis inhibitors and anti-PD-1/PD-L1 at present. The preliminary data of some combinations demonstrated favorable therapeutic effects such as camrelizumab plus apatinib in advanced triple-negative breast cancer (NCT03394287), advanced cervical cancer (NCT03816553), and advanced HCC (NCT03463876) and sintilimab plus anlotinib in advanced NSCLC (NCT03628521) and PD-L1-positive recurrent or metastatic cervical cancer ( 284 ). Subsequent phase 3 trials are necessary to confirm the effectiveness of these combination regimens.…”
Section: Therapeutic Trials To Validate Resistance Mechanismsmentioning
confidence: 99%
“…To date, 15 clinical trials have reported their findings for cervical cancer (Table 1), while another two clinical trials (78,79) are ongoing for advanced or metastatic cervical cancer. Among the reported clinical trials, two focused on pembrolizumab (16,17,(69)(70)(71), three on nivolumab (18-20), one on sintilimab (72), two on balstilimab (73,74), one on camrelizumab (75), two on cemiplimab (76, 77), one on atezolizumab (21). Afterwards, we would review the outcomes of pembrolizumab, nivolumab, and atezolizumab in detail and also prospect the ongoing clinical trials.…”
Section: Clinical Evidences For Pd-1/pd-l1 Icis In Cervical Cancermentioning
confidence: 99%